Impacto psicológico del covid 19 en un adulto mayor de 74 años del cantón Caluma provincia de Bolívar - Vargas Jimenez, Maria Eugenia (2022)
The present case study was carried out with the objective of determining the psychological impacts that an older adult refers as a result of the pandemic caused by COVID. All this was carried out through the use of clinical history, semi-structured interview, direct observation, and the application of psychological tests "Beck Depression Inventory", "Hamilton Anxiety Scale" and "Mini mental", in addition, the technique of Cognitive Behavioral Therapy "Registry of Cognitive Behavioral Therapy", the qualitative methodology that was used in this work was aimed at studying variables such as: COVID 19 and psychological impacts on an older adult, also thanks to the implementation of the CBT techniques, it was possible to meet the stated objective, on the other hand, through a therapeutic plan, it was possible to modify those thoughts that the patient expressed during the psychological intervention, in this way it was possible to mitigate the psychological impacts on the elderly due to the conditions of COVID 19, in this way great results were achieved in improving their quality of life, both personal and social.